Effects of evolocumab on plasma levels of proprotein convertase subtilisin/kexin type 9 and lipoprotein(a) in acute myocardial infarction. (25th November 2020) - Nakamura, A; Kanazawa, M; Kagaya, Y; Kondo, M; Sato, K; Endo, H; Nozaki, E
Abstract: Background: There are two types of circulating proprotein convertase subtilisin/kexin type 9 (PCSK9), mature and furin-cleaved. Most types of lipoprotein(a) [Lp(a)], an independent risk factor of cardiovascular events, bound to mature PCSK9. Purpose: This study examined the effects of monoclonal anti-PCSK9 antibody on plasma PCSK9 and Lp(a) levels in acute myocardial infarction (MI). Methods: Acute MI patients (n=36) were randomly divided into evolocumab (140 mg; n=17) and non-evolocumab (n=19) groups. Changes in plasma PCSK9 and Lp(a) levels were monitored before and 1, 3, 5, 10, and 20 days after evolocumab administration. Results: In the non-evolocumab group, plasma levels of mature PCSK9, furin-cleaved PCSK9, and Lp(a) (236.4±57.3 ng/mL, 22.4±5.8 ng/mL, and 19.2. ± 16.5 mg/dL, respectively) significantly increased by day 3 (408.8±77.1 ng/mL, P<0.001; 47.2±15.7 ng/mL, P<0.001; and 39.7±21.3 mg/dL, P<0.005, respectively) and returned to the baseline by day 10 or 20. In the evolocumab group, mature PCSK9 significantly increased by >1000 ng/mL with a simultaneous decline of furin-cleaved PCSK9 below the measurement sensitivity level after day 3. The incremental area under the curve for plasma Lp(a) levels was significantly smaller in the evolocumab group compared with the non-evolocumab group (P=0.038). Conclusion: Mature and furin-cleaved PCSK9 are transiently upregulated after MI onset. Evolocumab significantly increases mature PCSK9 and decreases furin-cleaved PCSK9 and might inhibit transient increase of plasma Lp(a) in acute MI. Funding Acknowledgement: Type of funding source: None